2022
DOI: 10.1038/s41467-022-28672-3
|View full text |Cite
|
Sign up to set email alerts
|

Air quality and health co-benefits of China’s carbon dioxide emissions peaking before 2030

Abstract: Recent evidence shows that carbon emissions in China are likely to peak ahead of 2030. However, the social and economic impacts of such an early carbon peak have rarely been assessed. Here we focus on the economic costs and health benefits of different carbon mitigation pathways, considering both possible socio-economic futures and varying ambitions of climate policies. We find that an early peak before 2030 in line with the 1.5 °C target could avoid ~118,000 and ~614,000 PM2.5 attributable deaths under the Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(75 citation statements)
references
References 56 publications
5
70
0
Order By: Relevance
“…The two major environmental strategic initiatives of "carbon peaking" and "carbon neutrality" are capable of coping positively with the dual conundrum of energy shortage and environmental degradation due to the overconsumption of fossil energy. [1][2][3][4] To this end, people are pinning their hopes on the exploitation and utilization of clean and renewable new energy sources. 5,6 As a new generation of green and sustainable energy source with zero carbon emission and high combustion calories, hydrogen energy has attracted more and more attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The two major environmental strategic initiatives of "carbon peaking" and "carbon neutrality" are capable of coping positively with the dual conundrum of energy shortage and environmental degradation due to the overconsumption of fossil energy. [1][2][3][4] To this end, people are pinning their hopes on the exploitation and utilization of clean and renewable new energy sources. 5,6 As a new generation of green and sustainable energy source with zero carbon emission and high combustion calories, hydrogen energy has attracted more and more attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, China has made initial achievements in addressing climate change and air pollution but still faces the dual pressures of carbon emission reduction and air quality improvement, and the potential for air pollutant reduction still needs to be further released [1]. Given the homogeneity of traditional greenhouse gases and air pollutant emission sources, climate policies will undoubtedly help accelerate air pollution improvements [2][3][4][5][6]. The contribution of climate policies and economic structural transformation to PM 2.5 exposure alleviation has become increasingly prominent in recent years in China [7].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of air pollution reduction, a previous study explored environmental inequality from inter-provincial trade (Dong et al, 2022), revealing that more than 70% of air pollution was embodied in national exports in less developed regions (Zhang et al, 2018). Tang et al reported that an early peak in carbon dioxide emissions had potential health benefits in China (Tang et al, 2022). Jiang et al found that the sulfur tax/nitrogen tax could cover the carbon intensity target using a computable general equilibrium (CGE) model (Jiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%